Gelsevirine is a novel STING-specific inhibitor and mitigates STING-related inflammation in sepsis - Chen, Yuhong; Bian, Huihui; Lv, Juan; Song, Wanxue; Xing, Chunlei; Hui, Chunlei; Zhang, Dinglei; Zhang, Chenxi; Zhao, Liang; Li, Yingke; Su, Li (Frontiers in Immunology, 2023)
Stimulator of IFN genes (STING) is central to production of interferon and proinflammatory cytokines in response to microbial DNA or self-DNA in the cytosol. The detrimental role of activation of STING during sepsis has been well documented. Here, we found that gelsevirine (GS) potently inhibit interferon and inflammatory cytokine induction in macrophages exposed to STING agonists (2'3'-cGAMP, IFN stimulatory DNA (ISD), and poly(dA:dT)). Then, in silico docking analysis and surface plasmon resonance binding study showed that GS bond with high affinity to the cyclic dinucleotide (CDN)-binding pocket of STING. Biotin pull-down assay also confirmed that GS competitively bond to STING protein. Furthermore, GS inhibited 2'3'-cGAMP-induced STING dimerization and subsequent activation. In addition, GS induced K48-linked STING ubiquitination and degradation, which was likely through upregulating and recruiting TRIM21. In mice exposed to cecal ligation and puncture (CLP)-induced sepsis, post-operative administration of GS significantly extended the survival period and mitigated acute organ damages. Overall, GS inhibited STING signaling by competitively binding to the CDN-binding pocket to lock STING in an inactive open conformation, while also promoting K48-linked STING ubiquitination and degradation. Our findings identify a novel STING-specific inhibitor that could be applied in the treatment of sepsis.